Correlation of immune cell subsets in the tumor microenvironment and peripheral blood with immunotherapy response in esophageal squamous cell carcinoma - Chen, Wei; Gong, Lian; Li, Yahu; Wu, Mengyao; Tao, Min (Frontiers in Immunology, 2025)
BackgroundEsophageal squamous cell carcinoma (ESCC) is commonly diagnosed at an advanced stage, where conventional chemoradiotherapy offers only limited clinical benefit. Immune checkpoint inhibitors targeting the tumor microenvironment (TME) have demonstrated substantial therapeutic potential; however, reliable biomarkers for predicting therapeutic outcomes remain unclear.MethodsSingle-cell RNA sequencing dataset for ESCC was obtained from the GEO database and analyzed using the Seurat R package to evaluate gene expression in tumor and adjacent tissues. Additionally, flow cytometry was used to assess immune cell subsets in peripheral blood samples from patients undergoing immunotherapy. Statistical analyses, including survival analysis and the Kruskal-Wallis test, were conducted to investigate the association between immune cell subsets and treatment efficacy.ResultsIn tumor tissues, immune subsets were significantly enriched compared with adjacent tissues, including CD8+ T cells with exhaustion (CD39, TIM3, PD-1) or activation/tissue residency (CD137, CD103) features; CD4+ T cells with activation (CD134, CD137) or regulatory (FOXP3) phenotypes; and dendritic cells expressing TIM3 or CD103. In peripheral blood, a median change in TIM3+ CD8+ T cells of 3.35% was observed following immunotherapy. Patients with changes exceeding this threshold experienced shorter progression-free survival (PFS) compared to those with lower changes (5.0 vs. 8.5 months, P = 0.024). Furthermore, TIM3+ CD8+ T cell changes were markedly reduced in patients achieving complete or partial responses compared to those with progressive disease.ConclusionsTIM3+ CD8+ T cells are a promising predictive biomarker for immunotherapy outcomes in ESCC. These findings highlight their potential to guide personalized treatment strategies in clinical practice.